4‐(2‐Hydroxyethyl)‐1‐piperazine ethane sulfonic acid repositioning: Amyloid disaggregating agent and its sustained‐release system. (15th November 2021) - Kim, Jaehoon; Kim, Dokyoung
Abstract: Here, we report the results of experiments regarding the chemical repositioning of 4‐(2‐hydroxyethyl)‐1‐piperazine ethane sulfonic acid (HEPES ), a representative buffering agent. In this work, we confirmed that HEPES could disaggregate amyloid plaques, a hallmark of Alzheimer's disease, and we verified its sustained‐release system (release for up to 2 weeks) via hybridization with a biocompatible polymer (Eudragit S100). Abstract : A chemical repositioning of 4‐[2‐hydroxyethyl]‐1‐piperazine ethane sulfonic acid (HEPES ) as an amyloid‐beta (Aβ) plaque disaggregating agent and its sustained‐release system were reported.